The Opportunity and Challenges of Implementing a Prototype Curriculum - Putri Irma Solikhah; Purnomo Purnomo (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Learning loss due to the Covid-19 pandemic prompted the simplification of the 2013 Curriculum into an Emergency Curriculum, which was then refined into a Prototype Curriculum. Curriculum changes always bring optimism as well as skepticism. The hope for a new curriculum that is better in line with the ability of education providers in implementation. This research is evaluative research with a literature study approach. This study aims to make a corrective contribution to the policy coherence of the prototype curriculum. The data source comes from government policies supported by expert analysis of curriculum developers. Data analysis is rationally deductive. It was concluded that the prototype curriculum focused on developing non-technical abilities and character within the framework of Pancasila values, simplifying learning materials, and developing literacy and numeracy skills. Opportunities from this curriculum are reducing the administrative burden of teaching, and the design of learning becomes more flexible so that the quality of learning can be improved. The challenge is the teacher's readiness (attitudes and emotions, knowledge, and behavior). Based on the Ministry of Education's recommendation, which refers to the results of the 2020 UKG, it is stated that the quality and competence of teachers are still low, it is necessary to improve IT capabilities, and the KKG and MGMP functions are not yet maximized.